1972
DOI: 10.2151/jmsj1965.50.2_71
|View full text |Cite
|
Sign up to set email alerts
|

Energy Budget of Wave Disturbances over the Marshall Islands During the Years of 1956 and 1958

Abstract: Based on the data in the Marshall Islands obtained in 1956 and 1958, vertical velocities and heat source associated with tropical wave disturbances are estimated and the energy transformation of the disturbances are examined. An approximate estimate of the upward transport of sensible and latent heat by small-scale convective motions is also obtained. Eddy available potential energy is generated by the heat of condensation and is transformed to the eddy kinetic energy in the upper troposphere centered about 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
56
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 19 publications
(17 reference statements)
11
56
1
Order By: Relevance
“…Recently, Lau and Lau (1990) utilized the 1980-1987 ECMWF analysis data to study statistically the synoptic-scale disturbances over the tropical oceans. Their results agreed with those by Nitta (1972) about the energetics of the western Pacific wave disturbances. From a theoretical point of view, Holton (1971) constructed a diagnostic model to study the characteristics of easterly waves.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…Recently, Lau and Lau (1990) utilized the 1980-1987 ECMWF analysis data to study statistically the synoptic-scale disturbances over the tropical oceans. Their results agreed with those by Nitta (1972) about the energetics of the western Pacific wave disturbances. From a theoretical point of view, Holton (1971) constructed a diagnostic model to study the characteristics of easterly waves.…”
Section: Introductionsupporting
confidence: 91%
“…These phenomena include ENSO (El Nino and Southern Oscillation), Madden and Julian Oscillation Julian, 1971 and1972), large-scale disturbances such as super cloud clusters, easterly waves and typhoons, and mesoscale disturbances such as cloud clusters and squall lines, etc. Numerical experiments suggest that phenomena with scales less than the MaddenJulian oscillation (30-60 day period and wavenumber one) appear to be organized and maintained by the convection-disturbance coupled mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, from the daily precipitation data (see for instance Figure 4(a)), an estimation of a 2D maximum heating field is obtained by a basic linear relation: a maximum heating of 5 K day −1 corresponds to 1 cm day −1 . These values fall within the range of estimated heating maxima from retrieval algorithms (4-6 K day −1 for 1 cm day −1 can be found in Tao et al (2001)) and from diagnostic budget studies over different geographic locations (4-10 K day −1 in 1 cm day −1 is suggested by Reed and Recker (1971); see also Nitta (1972), Johnson (1976), Thompson et al (1979), Chong and Hauser (1990) and Lin and Johnson (1996)). …”
Section: Elaboration Of Pv Anomaliessupporting
confidence: 80%
“…For t z z we utilize the empirical formula of Hong and Wang (1980), which is based on the work of Reed and Recker (1971) and Nitta (1972):…”
Section: Heating Pro®le and Other Gswm Parametersmentioning
confidence: 99%